Coupled orbital and ENSO forcing shaped the Holocene evolution of East Asian precipitation patterns - Anguo Xiao; Yanzhen Li; Teng Liu; Ze Zhang; Simin Jin; Ruiyao Zhang; Xiaosong Chen; Chunju Huang (Quaternary Science Reviews, 2026)

Functional analysis of the mitochondrial cytochrome b gene Cob085 in stress responses, appressorium formation, and pathogenicity of Magnaporthe oryzae - Nihal Niaz; Haseeb Younis; Zhe Ni; Peng Guo; Zhiguo Ren; Xinyang Liu; Anguo Ding; Junhua Zhang (Physiological and Molecular Plant Pathology, 2026)

Sensitive and rapid detection of allergenic β-conglycinin α-subunit in soy products: From quantum dot nanobeads fluorescence-linked immunosorbent assay development to recognition mechanisms exploration - Anguo Liu; Yuanhe Yang; Jiye Li; Jinyan Li; Zhen Li; Xiaoyun Zhao; Pingli He (Chemical Engineering Journal, 2026)

Engineered probiotic carriers enregulate coordinated cuproptosis and ferroptosis with immune activation against bladder cancer - Anguo Zhao; Rongkang Li; Rui Liang; Qi Zhuang; Yang Liu; Dashi Deng; Peng Yu; Lei Peng; Hongbo Xu; Jun Zhang; Zhangxin He; Xin Chen; et al. (Chemical Engineering Journal, 2026)

From untargeted discovery to targeted quantification: Discovery of characteristic peptides for quantitative monitoring of allergen degradation in fermented soybean meal - Anguo Liu; Jiye Li; Yuanhe Yang; Zhen Li; Pingli He (Food Chemistry, 2026)

Semi-anchored percolation networks for low-threshold and selective desalination in FCDI - Lirong Bi; Xinwei Sui; Shuo Tian; Xiaowei Liu; Shicheng Ma; Zhongqiu Liu; Yujing Liu; Anguo Ying (Desalination, 2025)

Phosphorylated Scrophularia ningpoensis polysaccharides mitigate oxidative stress and modulate immunity by regulating the gut microbiota in cyclophosphamide-treated mice - Lufen Huang; Jianan Wang; Litao Wang; Shuling Liu; Xinru Niu; Zhouwen Wu; Kexin Guo; Si Gong; Bowen Wei; Zhaochun Wang; Jianing Mi; Yufeng Liu; et al. (Food Bioscience, 2025)

NiFe2O4/Ni3Fe nanoparticles Decorate wood carbon strategies for efficient electromagnetic absorption - Anguo Cui; Yukun Miao; Chang Wang; Zhongning Tian; Qianqian Jia; Jinyuan Liu; Guanying Song; Ting Wang; Zhenjiang Li; Meng Zhang (Chemical Engineering Journal, 2025)

Synergistic enhancement of catalytic hydrodeoxygenation performance by oxygen vacancies and frustrated Lewis pairs - Qing-Qing Sun; Cong Liu; Guo-Qiang Zhang; Zhong-Qiu Liu; Mei-Ying Wang; Ai-Min Wang; Yujing Liu; Runpu Shen; Anguo Ying (Fuel, 2025)

Research on the effectiveness of LDAR and precise emission reduction strategies of five typical petrochemical companies - Anguo Dai; Shujie Zhao; Shuaijie Yuan; Rentao Liu; Bowen Liang; Zhigang Liu (Journal of Cleaner Production, 2025)

Synergistic regulation of dual thresholds: Hydroxyl occupancy and carbon species in the targeted catalytic hydrocracking of lignite - Cong Liu; Zhi-Ang Liu; Zhong-Qiu Liu; Hai-Ni Yang; Guo-Xiao-Yao Zhao; Yujing Liu; Anguo Ying (Chemical Engineering Journal, 2024)

Orbital and suborbital climate cycles recorded in terrestrial strata from the late Paleocene-early Eocene in the Subei Basin, East China - Juan Liu; Yanzhen Li; Liangcheng Tan; Rui Zhang; Xingxing Liu; Ze Zhang; Anguo Xiao; David B. Kemp; Chunju Huang (Global and Planetary Change, 2024)

Novel photic responsive Janus nanoparticles: Interfacial catalysts for efficient preparation of biodiesel - Mingshu Li; Rong Zhang; Chuanxing Jia; Zhongqiu Liu; Yujing Liu; Anguo Ying (Fuel, 2024)

Astronomical forcing of terrestrial organic carbon burial in East Asia during the Eocene - Juan Liu; Juye Shi; Yongchao Lu; Xiaojie Fan; Ze Zhang; Rui Zhang; Zhixiang Wang; Ke Xu; Anguo Xiao; David B. Kemp; Chunju Huang (Earth and Planetary Science Letters, 2024)

Astronomically forced climate evolution in the North China Plain since the Late Pliocene - Mengmeng Cao; Fubing He; Yubin Cui; Jingbo Ni; Kai Wang; Wenzhi Niu; Lingyan Bai; Yueze Zhang; Xiaoyong Liu; Anguo Wang; Guanghong Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

An intelligent dual stimuli-responsive Pickering emulsion for highly efficiently producing waste frying oil-based biodiesel - Jia-Liang Guo; Qing-Qing Sun; Zhong-Qiu Liu; Feng-Xiang Wang; Tingjun Fu; Yujing Liu; Anguo Ying (Journal of Cleaner Production, 2024)

Silver nanocluster-based aptasensor for the label-free and enzyme-free detection of ochratoxin A - Runxian Li; Longjiao Zhu; Min Yang; Anguo Liu; Wentao Xu; Pingli He (Food Chemistry, 2024)

Two birds with one stone: A magneto-optical dual-stimuli-responsive intelligent Pickering emulsion for efficient conversion of glucose to 5-hydroxymethylfurfural - Zhong-Qiu Liu; Jia-Liang Guo; Rong-Hua Liang; Feng-Xiang Wang; Zhan-Ku Li; Yujing Liu; Anguo Ying (Chemical Engineering Journal, 2024)

Simultaneous detection of glycinin and β-conglycinin in processed soybean products by high-performance liquid chromatography-tandem mass spectrometry with stable isotope-labeled standard peptides - Anguo Liu; Luqing Yang; Yuanhe Yang; Siqi Lei; Zhen Li; Pingli He (Food Research International, 2023)

Sandwich like poly(ionic liquid)s functionalized microspheres: Efficient interfacial catalysts for preparation of biodiesel - Anguo Ying; Mingshu Li; Xiaotong Lu; Shengnan Li; Limin Wang; Zhongqiu Liu; Yujing Liu (Chemical Engineering Journal, 2023)

Synthesis of novel magnetic pitch-based hypercrosslinked polymers as adsorbents for effective recovery of Ag+ with high selectivity - Qi Peng; Hongwei Zhao; Guang Chen; Qilin Yang; Xinxiu Cao; Shaohui Xiong; Anguo Xiao; Gen Li; Bo Liu; Qingquan Liu (Journal of Environmental Management, 2023)

Polyacrylonitrile fiber with light-driven intelligent reversible and switchable wettability as an environmental benign solid base for biodiesel production - Huan-Xing Zhou; Qing-Qing Sun; Zhong-Qiu Liu; Jie-Wen Duan; Tingjun Fu; Yujing Liu; Anguo Ying (Journal of Cleaner Production, 2023)

PANF supported polymeric ionic liquids: Amphiphilic microenvironment for efficient preparation of biodiesel - Linsheng Bai; Limin Wang; Yujing Liu; Zhongqiu Liu; Anguo Ying (Fuel, 2023)

Multi-functional flame retardant coatings comprising chitosan/ gelatin and sodium phytate for rigid polyurethane foams - Wufei Tang; Guoqi Liang; Lei Wang; Yi Yuan; Wubliker Dessie; Fang Liu; Zuodong Qin; Yi Wang; Anguo Xiao; Xiaodong Jin (Journal of Cleaner Production, 2023)

Effect of fixed time interval of rainfall data on calculation of rainfall erosivity in the humid area of south China - Anguo Tu; Songhua Xie; Ying Li; Zhao Liu; Faxing Shen (CATENA, 2023)

Development and application of novel InDel markers in flax (Linum usitatissimum L.) through whole-genome re-sequencing - Hui Jiang; Gen Pan; Touming Liu; Li Chang; Siqi Huang; Huijuan Tang; Yuan Guo; Yena Wu; Jie Tao; Anguo Chen (Genetic Resources and Crop Evolution, 2022)

Response of Microbial Communities on Culturing Plates of Post-settlement Sea Cucumbers to Seawater Acidification and Warming - Hongxia Zhang; Mingshan Song; Lili Wang; Anguo Zhang; Xiaolong Yang; Yongjian Liu; Xiutang Yuan (Frontiers in Marine Science, 2021)
Seawater acidification and warming have been found to affect the early life of many marine organisms, but their effects on the microbial community in the environment related to the early development stage of aquaculture species have been rarely investigated. To understand how seawater acidification and warming impact the microbial community in aquaculture systems, we designed four microcosms to monitor and characterize the microbial composition on the corrugated plates in the Apostichopus japonicus culture tanks during its post-settlement stage. High-throughput 16S rRNA sequencing revealed that the bacterial community composition varied significantly in different periods of incubation. The bacterial diversity and community composition were obviously changed by seawater acidification and warming in the early period and then tended to revert to the level of the control group. Acidification significantly increased the relative abundance of dominant families Rhodobacteraceae and Flavobacteriaceae in the early period, suggesting that microbiota could increase the abundance of predominant taxa to adapt to increased CO 2 concentration and reconstruct a stable community structure. No interaction effect of both factors was observed in the combined group. Results reveal that the microbial communities on the corrugated plates in A. japonicus culture tank were affected in the early period of incubation, and could then acclimatize to the increased CO 2 and temperature. This study provides new insights into the variation and adaptation responses of the microbiota in aquaculture systems to seawater acidification and warming.

Levels, Sources and Potential Risks of Polychlorinated Biphenyls and Organochlorine Pesticides in Sediments of Qingduizi Bay, China: Does Developing Mariculture Matter? - Xiaolong Yang; Lili Wang; Anguo Zhang; Xing Liu; Gorka Bidegain; Humin Zong; Chunjiang Guan; Mingshan Song; Liang Qu; Wei Huang; Xiutang Yuan (Frontiers in Marine Science, 2019)

Analysis of chemical characteristics of PM2.5 in Beijing over a 1-year period - Zhanshan Wang; Dawei Zhang; Baoxian Liu; Yunting Li; Tian Chen; Feng Sun; Dongyan Yang; Yunping Liang; Miao Chang; Liu Yang; Anguo Lin (Journal of Atmospheric Chemistry, 2016)

Polychlorinated biphenyls and organochlorine pesticides in surface sediments from the sand flats of Shuangtaizi Estuary, China: levels, distribution, and possible sources - Xiutang Yuan; Xiaolong Yang; Guangshui Na; Anguo Zhang; Yuze Mao; Guize Liu; Lili Wang; Xiaodong Li (Environmental Science and Pollution Research, 2015)

Applications of Hyperspectral Imaging in Chicken Meat Safety and Quality Detection and Evaluation: A Review - Zhenjie Xiong; Anguo Xie; Da-Wen Sun; Xin-An Zeng; Dan Liu (Critical Reviews in Food Science and Nutrition, 2015)

Hepatoprotective Activity of CrPic against Alloxan-Induced Hepatotoxicity in Mice - Weijiang Fan; Anjun Liu; Wenhang Wang; Guoqiang Zheng; Anguo Teng (Biological Trace Element Research, 2012)

A simple quasi-geostrophic coupled ocean-atmosphere model - Liu Shikuo; He Anguo (Advances in Atmospheric Sciences, 1991)